LEGAL POLICY ON SIDE EFFECT OF THE COVID-19 VACCINE ACCORDING TO HEALTH LAW - Yusriando Yusriando; Willy Tanjaya; Ramanathan Ramanathan (Magister Kenotariatan Universitas Pasundan, 2021)
Health of the Republic of Indonesia Number: 10 of 2021 concerning the Implementation of Vaccination in the Context of Combating the Corona Virus Disease 2019 (Covid19) Pandemic which refers to Law Number: 36 of 2009 concerning Health , Law Number: 4 of 1984 concerning Outbreaks of Infectious Diseases and Law Number 6 of 2018 concerning Health Quarantine. According to the regulation of the minister of health that vaccination is carried out at health facilities, however, vaccination can be carried out outside health facilities; The government's responsibility for the side effects of the covid-19 vaccine has not yet been seen in the community so that it has the impact of refusing vaccination because the most fatal side effect of the covid-19 vaccination is that it can cause death apart from concerns about the halalness of the covid-19 vaccine In addition, there is no specific rule regarding compensation as referred to in the existing regulations for people who die after being vaccinated;The legal impact if the community refuses to be vaccinated can be given sanctions based on the Regulation of the Minister of Health of the Republic of Indonesia Number: 10 of 2021 concerning the Implementation of Vaccination in the Context of Combating the 2019 Corona Virus Disease (Covid19) Pandemic which is linked to Article 14 paragraph (1) of the Republic of Indonesia Law Number: 4 1984 concerning Outbreaks of Infectious Diseases, but the narrative of the article in question is not in line with the intention of refusing vaccines so that it can lead to multiple interpretations in enforcing sanctions on people who refuse to be vaccinated.